2012
DOI: 10.1007/s00441-012-1334-7
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule-induced Rho-inhibition: NSAIDs after spinal cord injury

Abstract: Limited axonal plasticity within the central nervous system (CNS) is a major restriction for functional recovery after CNS injury. The small GTPase RhoA is a key molecule of the converging downstream cascade that leads to the inhibition of axonal re-growth. The Rho-pathway integrates growth inhibitory signals derived from extracellular cues, such as chondroitin sulfate proteoglycans, Nogo-A, myelin-associated glycoprotein, oligodendrocyte-myelin glycoprotein, Ephrins and repulsive guidance molecule-A, into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 121 publications
(245 reference statements)
1
54
1
1
Order By: Relevance
“…By considering the fact that the inhibition of inflammation results in preventing further neural damage, the administration of some conventional medications such as NSAIDs has been proposed so far. In this regard, Kopp et al 52 showed that ibuprofen which is a Food and Drug Administration-approved NSAID can enhance axonal regeneration by inhibiting the small GTPase RhoA molecule. Furthermore, Kwon et al 10 has expressed the efficacy of various medications including erythropoietin, NSAIDs, antiCD11d antibodies, minocycline, progesterone, estrogen, magnesium, riluzole, polyethylene glycol, atorvastatin, inosine, and pioglitazone as neuroprotective treatments for acute SCI in a systematic review on animal models.…”
Section: Discussionmentioning
confidence: 99%
“…By considering the fact that the inhibition of inflammation results in preventing further neural damage, the administration of some conventional medications such as NSAIDs has been proposed so far. In this regard, Kopp et al 52 showed that ibuprofen which is a Food and Drug Administration-approved NSAID can enhance axonal regeneration by inhibiting the small GTPase RhoA molecule. Furthermore, Kwon et al 10 has expressed the efficacy of various medications including erythropoietin, NSAIDs, antiCD11d antibodies, minocycline, progesterone, estrogen, magnesium, riluzole, polyethylene glycol, atorvastatin, inosine, and pioglitazone as neuroprotective treatments for acute SCI in a systematic review on animal models.…”
Section: Discussionmentioning
confidence: 99%
“…Myelin and myelin debris contain several myelin-associated molecules that inhibit regeneration [33][34][35] , among which the Nogo-A N-terminal region (amino-Nogo-A) is one of the most potent inhibitors. inhibition of Nogo-A increases axon plasticity and regeneration and improves functional recovery [36][37][38] .…”
Section: Chabc and Blocking Myelin Inhibitorsmentioning
confidence: 99%
“…For example, the widely used nonsteroidal anti-inflammatory drug ibuprofen was shown to possess a second molecular action: inhibiting the cytoskeletal regulating GTPase RhoA 7 . This led to preclinical use of ibuprofen in promoting axonal growth after spinal injury 8,9 , and a clinical trial has now started to assess its potential in traumatic spinal cord injury (ClinicalTrials.gov NCT02096913). However, in other cases, certain compounds never succeeded in their intended application and then are resurrected for new uses.…”
mentioning
confidence: 99%